Representasi Taktil sebagai Strategi Adaptif dalam Pembelajaran Notasi Musik bagi Mahasiswa Disabilitas Netra: Studi Kasus pada Mata Kuliah Teori Musik - Reizki Habibullah; Winny Chrisan Alya (Universitas Negeri Medan, 2026)
Learning music notation for visually impaired students faces challenges because the staff system and accidental markings are presented visually. This study aims to examine the use of tactile representation as an adaptive strategy in the Music Theory course in the Ethnomusicology Study Program at the Indonesian Institute of the Arts, Surakarta. The study used a qualitative approach with a case study design. Data were obtained through observation, in-depth interviews with lecturers and visually impaired students, and documentation, then analyzed thematically. The results showed that lecturers used the five fingers of the left hand to represent the five lines of the staff, while variations in finger touch were used to introduce accidental markings. This strategy allows students to understand pitch positions through tactile and auditory experiences without the need for special aids. Although effective for basic material, this method is still limited to certain learning contexts. The research findings emphasize the importance of adaptive pedagogical innovation in creating inclusive and equitable music theory learning for visually impaired students.